Language Ideologies Among Kamënẗsá Biyá People in Sibundoy Valley (Colombia): Identity, Use, Transmission, Preservation - Barón Sotto, Jaime Alejandro; Múnera, Adrián (Íkala, Revista de Lenguaje y Cultura, 2025)
This qualitative ethnographic article analyzes the linguistic ideologies of the Kamënts̈á Biyá people from the Sibundoy Valley to understand their language use practices, the influence of Spanish on identity and intergenerational transmission, and their implications on domains of use and language preservation. The study involved 11 community participants and was based on a sociolinguistic, decolonial ethnographic and participant observation perspectives. The results indicate that, in addition to its identity and ceremonial significance, linguistic ideologies modulate the daily circulation of the language, either restricting or expanding domains of use beyond migration and contact with Spanish. However, revitalization strategies, such as bilingual intercultural education, community radio, and the recovery of ritual spaces, strengthen the language identity and use. We discuss dynamics of linguistic ideologies, language as a symbol of identity, and preservation efforts of indigenous communities in related studies. In conclusion, for a linguistic revitalization beyond teaching, it is necessary to design strategies linking cultural practices and strengthening intergenerational ties.